Fuzzy logic controller for roof sprinkler cooling system / Faizzudin Sahazudin , Nooraini Yusoff and Fadzilah Siraj - Yusoff, Nooraini; Sahazudin, Faizzudin; Siraj, Fadzilah (Unit Penerbitan UiTM Kelantan, 2018)
In Malaysia, a cooling system is very efficient in reducing the heat from outside temperature. Normally, for those who afford, the best equipment will be utilized to make homes in a cool and comfort temperature. This may take an equipment such as air-conditioner or super insulation to their house. However, those equipments are costly for their installation, maintenance and energy. In this study, we propose a design of roof sprinkler cooling system using fuzzy logic (FL). The water sprinkler works by triggering the controller to open the valves to release and spray water. FL could benefit the cooling system by intelligently controlling the actual water quantity based on the observed daily weather condition captured from a sensor. This technique is the key approach to saving both water and energy. The system has been simulated and tested accordingly with a number of conditions and parameters, and it has been shown that the proposed design is feasible and practical to be implemented.